Divergent platforms - Sophie Bade (Max Planck Institute for Research on Collective Goods, 2011)
A robust feature of models of electoral competition between two opportunistic, purely office-motivated parties is that both parties become indistinguishable in equilibrium. I this short note, I show that this strong connection between the office motivation of parties and their equilibrium choice of identical platforms depends on the following two - possibly counterfactual - assumptions: 1. Issue spaces are uni-dimensional and 2. Parties are unitary actors whose preferences can be represented by expected utility functions. The main goal here is to provide an example of a two-party model in which parties offer substantially different platforms in equilibrium even though no exogenous asymmetries are assumed. In this example, some voters' preferences over the 2-dimensional issue space are assumed to exhibit non-convexities and parties evaluate their actions with respect to a set of beliefs on the electorate.
Keywords: C79; D72; D81; 330; Downs Model; Games with Incomplete Preferences; Platform Divergence; Knightian Uncertainty; Uncertainty Aversion.; Wahlkampf; Parteiprogramm; Median Voter; Spieltheorie; Präferenztheorie; Entscheidung bei Unsicherheit; Theorie